Social Integration in Multicultural Societies: A Qualitative Study - Jamiludin; Alimin Alwi; Ambo Upe (Jurnal Ilmu Sosial dan Humaniora, 2023)
Since the settlement of the Transmigration community in 1983-2023, there has never been conflict and disintegration, as is the case in other multicultural societies that tend to conflict. This study aims to find out why the Multicultural Community in West Muna Regency is integrated and what values of social integration have been built. Methodologically, the data for this study were obtained using in-depth interviews, participant observation, and documentation studies, all of which are descriptive qualitative methods. The results of this study show that the multicultural community in West Muna Regency is integrated because human nature wants peace where every individual wants peace and comfort of life, which is externalized in the form of behavior in daily life both in family, neighbors and community;  as social beings in mutual need between nations of different tribes and different religions; religious reasons in which each community of a different religion obeys religious orders and tolerance with people of different religions; and cultural reasons that are the ancestral teachings of each tribe that each tribe adheres to are different. There is a binding value that represents the interests of all religions and tribes, namely the value of peace. The value of social integration in a multicultural society is the value of peace consisting of social cohesion, namely the unification of religious, cultural, and occupational equality, and social adhesion, namely unification based on differences in religion, culture, and work.